El acento castellano desde una pespectiva analógica - Bárkányi, Zsuzsanna (Acta Hispanica, 2009)
In this study we argue that the stress system of nominals in Spanish can be captured more accurately in an anological framework than in more traditional rule-based approaches. We back up our claim with a nonce word experiment carried out with 40 native speakers of Spanish.